Regional Economic Outlook, October 2018, Asia Pacific : Asia at the Forefront: Growth Challenges for the Next Decade and Beyond. (Regional Economic Outlook, 2018)
Growth in the first half of 2018 was softer than in 2017, especially in advanced economies. In contrast, growth remained robust in emerging market economies and broadly in line with expectations. After rising to 6.9 percent in 2017, growth in China continued to be strong into the first half of 2018 but has likely slowed since, given the latest high-frequency indicators, including weakening investment growth. In Japan, after exceeding potential for two years, growth dropped into negative territory in the first quarter of 2018 before rebounding sharply in the second quarter. In India, growth continues to recover steadily after the disruptions related to demonetization and the rollout of the goods and services tax in the last fiscal year.1 And in ASEAN-4 economies (Indonesia, Malaysia, the Philippines, Thailand), growth generally lost momentum in the first half of 2018, except in Thailand.